A cyclic iterative method for solving a class of variational inequalities in Hilbert spaces. (3rd October 2018) - Tuyen, Truong Minh
ABSTRACT: The purpose of this paper is to introduce a new iterative method for solving a variational inequality over the set of common fixed points of a finite family of sequences of nearly non-expansive mappings in a real Hilbert space. And, using this result, we give some applications to the problem of finding a common fixed point of non-expansive mappings or non-expansive semigroups and the problem of finding a common null point of monotone operators.